Influence of local anaesthesia on the quality of class II glass ionomer restorations - NANDA VAN DE HOEF & EVERT VAN AMERONGEN (IAPD and Blackwell, 2007)
To investigate the influence of local anaesthesia on the quality of class II glass ionomer restorations with discomfort as cofactor.